Advertising of legal services: Perceptions of attorneys - C. Boshoff (South African Journal of Business Management, 1990)
Professional practitioners are increasingly questioning the status quo with regard to restrictions on the advertising of professional services. It occurs against the background of developments such as deregulation and increased competition from non-professionals. Professional associations are largely uncertain how to address the Issue. This study is an attempt to contribute towards the debate concerning advertising in the legal profession. It reports on a survey among 1 000 practising attorneys. The study found that attorneys are generally in favour of advertising their services, but believe that it should be conducted within the confines of certain specified guidelines.
Keywords: 650